FEM Optimisation of Seepage Control System Used for Base Stability of Excavation - Ouzaid, Ilyes; Benmebarek, Naïma; Benmebarek, Sadok (Salehan Institute of Higher Education, 2020)
With the existence of a high groundwater level, the head difference between the inside and outside of an excavation may lead to the loss of stability of the excavation’s surface. Hence, a fundamental understanding of this occurrence is important for the design and construction of water-retaining structures. In some cases, the failure mechanism cannot be predicted exactly because of its mechanical complexity as well as a major lack of protection systems and not adopting effective countermeasures against this phenomenon. The article took a tranche from an 80 km long open sewer located in the Ruhr area, Germany as an example to establish a hydro-geological model and analyse the instability of the excavation base surface caused by the groundwater flow at 45m deep and to present the effectivity of an adopted drainage system inside the excavation pit as 39 columns of sand to relax the pore water pressure. By using the Finite Element Method (FEM) analysis, the failure mechanism was investigated before applying any countermeasures, and the total length of the adopted countermeasure system was minimised. Also, various position tests were performed on the adopted drainage system to confirm the optimised position. The results of this numerical study allowed the deduction of the importance of the used drainage system by achieving 44% more in the excavating process. After achieving the required excavation depth, a further increase of the sand columns’ penetration may be considered non-economic because, after adding extra depth, all the situations have the same safety factor. In addition, this can provide a reference for the optimised position of the sand columns where they must be applied right by the wall and limited by a critical distance, D/2, half of the embedded depth of the wall.